Characterization of highly substituted, cationic amphiphilic starch derivatives: Dynamic surface tension and intrinsic viscosity. Issue 11 (7th June 2013) - Genest, Sabine; Schwarz, Simona; Petzold‐Welcke, Katrin; Heinze, Thomas; Voit, Brigitte
<x xml:space="preserve">Abstract</x> The surface activity and viscometric behavior of highly substituted, amphiphilic polysaccharides, derived from potato starch by modification with benzyl‐ and hydroxypropyl‐trimethylammonium groups, are studied in salt‐free and 0.05 M NaCl aqueous solution. For the first time dynamic surface tension measurements of amphiphilic starch derivatives have been effected using the pendant drop method and it was possible to correlate them with particle sizes and apparent charge density. Rheological investigation of large concentration ranges (0.01–20 g/L) is used to discuss Huggins plots and typical polyelectrolyte (PEL) behavior for all starch derivative samples could be found. The determination of overlap concentration and, in dilute aqueous solution, of intrinsic viscosity was possible. For the latter one the semi‐empirical equation of Rao was used, making it possible to get insights to PEL conformation in dependence on the degrees of substitution (DS) of both substituents. It is shown that for intrinsic viscosity an inversion of the impact of both substituents takes place, with hydrophobic benzyl groups on the one hand and cationic hydroxypropyl‐trimethylammonium groups on the other. Data evaluation via the ratio of both DS values had been successfully utilized and thus, the applied method has been identified as being a promising tool to compare a multitude of starch derivatives with substituents of different polarity in various DS to get tendencies regarding overall hydrophobicity.